1st International Conference of the revival of applied arts, crafts and beliefs of the peoples of Sayan-Altai uplands (July 24–27, 2016, Kyzyl) - Kyrgys, Zoya K. (The New Research of Tuva, 2016)
This is a review of the International Conference of the revival of applied arts, crafts and beliefs of the peoples of Sayan-Altai uplands, which aimed to provide support for artisan craftwork and other forms of applied folk art. The conference was held in the city of Kyzyl on July 24-27, 2016. It was co-organized by Khoomei International Research Center (Kyzyl, Republic of Tuva), Tuvan State University and the Center for the Development of Traditional Tuvan Culture and Crafts (Republic of Tuva). Among the conference participants were scholars from the USA, Austria, Republic of Tuva (Russia) and expert craftsmen from Tuva and the regions of the Altai.Discussions at the conference sessions touched such issues as the historical and cultural heritage of the peoples of the Sayans and the Altai and its role in contemporary life; continuity in cultural development; Tuvan traditional beliefs; revival of spiritual culture; the triad in shamanic spirituality; Tuvan applied arts, etc. Applied arts preserve specific features of the ethnic world view common for a number of peoples of the Sayan-Altai uplands. Conference participants highly appreciated the work of the leading master stonecutters, makers of ethnic costume, tools and expert practitioners of other traditional arts. Also discussed were the problems of artistic and professional growth, contemporary uses of applied arts, and the importance of studying applied arts as a reflection of ethnic culture.The conference also included an international symposium on “Woodcarving in Central Asian crafts”. An exhibition featured decorative and ornamental art, horsehair and leather strap items, stonecutting, furriery, etc. The contest brought together 200 craftsmen, 34 of whom took part in the final exhibition.The article lists the recommendations that the conference suggested government agencies of the Republic of Tuva and other institutions should follow to coordinate the support of contemporary applied art in Tuva. Among these agencies and institutions are the regional Ministries of Culture, Education, Economics, and Labor, Aldan Maadyr National Museum, Khoomei International Research Center, etc.
Keywords: 2016 conference; applied art; cultural heritage; people of the Sayans and Altai; review; resolution